2020
DOI: 10.1007/s00338-020-02004-7
|View full text |Cite
|
Sign up to set email alerts
|

A unique reproductive strategy in the mushroom coral Fungia fungites

Abstract: The vast majority of scleractinian corals are either simultaneous hermaphrodites or gonochoric. Exceptions to these are rare. Nevertheless, species belonging to the family Fungiidae are known to exhibit a wide variety of reproductive strategies. We examined the reproductive ecology of the mushroom coral Fungia fungites in Okinawa. Our study was conducted as part of a long-term, wide-ranging project (2009-2010 and 2013-2017) which explored the unique reproductive strategies of several species belonging to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The coral Lobactis scutaria has been found to exude large amounts of nematocyst-enriched mucus when in contact with neighbouring corals (Chadwick, 1988), and to begin producing and releasing gametes as early as 1.5 years old and as small as 25 mm (Goffredo and Chadwick-Furman, 2003). In conjunction with the mobility of free-living species and their capacity to shed sediments (Bongaerts et al, 2012;Hoeksema and Bongaerts, 2016), fungiid corals have been shown to be highly plastic in their reproductive methods (Eyal-Shaham et al, 2020) and be well-suited to thrive in various reef environments (Hoeksema and Moka, 1989;Chadwick-Furman and Loya, 1992;Hoeksema, 2012b;Hoeksema, 2012a).…”
Section: Competitive Advantagesmentioning
confidence: 99%
“…The coral Lobactis scutaria has been found to exude large amounts of nematocyst-enriched mucus when in contact with neighbouring corals (Chadwick, 1988), and to begin producing and releasing gametes as early as 1.5 years old and as small as 25 mm (Goffredo and Chadwick-Furman, 2003). In conjunction with the mobility of free-living species and their capacity to shed sediments (Bongaerts et al, 2012;Hoeksema and Bongaerts, 2016), fungiid corals have been shown to be highly plastic in their reproductive methods (Eyal-Shaham et al, 2020) and be well-suited to thrive in various reef environments (Hoeksema and Moka, 1989;Chadwick-Furman and Loya, 1992;Hoeksema, 2012b;Hoeksema, 2012a).…”
Section: Competitive Advantagesmentioning
confidence: 99%
“…However, the literature suggested that F. fungites might differ in reproductive mode across its range, potentially enabling a comparison of energy investment between spawning and brooding for a single species. F. fungites is common in Okinawa (Loya and Sakai, 2008) where it has a protracted, four-month reproductive season, during which brooded planulae are released daily for 4-6 weeks (Munasik, 1999;Loya et al, 2009;Eyal-Shaham et al, 2020). In contrast to the Okinawa population, the only record to date for reproduction of F. fungites on the GBR implies that there it behaves as a broadcast spawner (Willis et al, 1985; but note that no available data on the reproductive cycle of this species on the GBR).…”
Section: Introductionmentioning
confidence: 99%
“…Evolution processes through sexual reproduction and gene-shuffling is the primary adaptive capability to environmental changes and enabling extension to and occupation of new ecological niches (Rundle et al 2006). In shallow corals, diverse strategies of sexuality were discovered during recent years (Baird et al 2009; Harrison 2011; Eyal-Shaham et al 2019; Eyal-Shaham et al 2020) and references within) but our knowledge of the reproduction of MCE corals remains limited (Shlesinger and Loya 2019).…”
Section: Introductionmentioning
confidence: 99%